Values and social-emotional competencies training for teachers after a decade of innovation - Palomera, Raquel; Briones, Elena; Gómez-Linares, Alicia (Universidad Pedagógica y Tecnológica de Colombia, 2019)
A teacher needs to have the skills to communicate and to interact positively with different actors in the education community and with students; he needs to have the ability to carry out auto-regulation and hetero-regulation processes; he needs to have the competencies to lead and manage the class, he must also know how to work in teams; he needs to have the capacity to make responsible and ethical decisions in order to solve problems in the context of education. The new subject called Values and Personal Competencies Training for Teachers aims both to improve the quality of education on the part of teachers and to improve student learning. The latter is at the heart of an active, dialogical, and collaborative teaching-learning process in their training in values and personal competencies, which are useful both in terms of personal life and in terms of professional life. This is a pioneering project at national and international levels in the implementation of values and personal competencies training on a mandatory basis in teaching degrees. This work presents a review of the resulting innovations since its creation in 2010.